META ANALYSIS OF THE EFFECT OF THE USE OF PhET SIMULATION ON LEARNING OUTCOMES OF PHYSICS OF SMA/MA STUDENTS - Delufi Mei Wendra; Festiyed Festiyed (PILLAR OF PHYSICS EDUCATION, 2022)
PhET simulation is an interactive learning simulation that has been widely studied by previous researchers. This study aims to determine the effect size using the meta-analysis method from previous studies.This type of research is a meta-analysis research. Meta-analysis is research that summarizes research data that has been previously researched and the data are quantitative. The articles analyzed were 26 articles. Data analysis technique is done by calculating effect size using Cohen's equation.The results of the study: the effect size value of the effect of using PhET simulation on learning outcomes of 0.723 is classified as moderate and it is proven that the use of PhET simulation is effectively applied to improve physics learning outcomes of SMA/MA students. The highest category effect size values obtained are: First, it occurs at the level of class X [ES 0.898] with the level of confidence in the data in class XI. Second, on the Fluid material [ES 1.174] with a high level of confidence the data on the Elasticity material. Third, the Demonstration method [ES 1.08] with a high level of confidence in the data on the Simulation method. Fourth, the Conceptual Change model [ES 1.040] with a high level of confidence in the data on the Discovery Learning model. Fifth, on the Skill aspect [ES 0.795] with a high level of confidence in the data on the Knowledge aspect.